2014
DOI: 10.1155/2014/890842
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Hepatoprotective Plants Used in Saudi Traditional Medicine

Abstract: Liver disease is one of the major causes of morbidity and mortality across the world. According to WHO estimates, about 500 million people are living with chronic hepatitis infections resulting in the death of over one million people annually. Medicinal plants serve as a vital source of potentially useful new compounds for the development of effective therapy to combat liver problems. Moreover herbal products have the advantage of better affordability and acceptability, better compatibility with the human body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 167 publications
(175 reference statements)
1
42
0
Order By: Relevance
“…polyphenols, tannins composed of some gallic and mostly ellagic acid, flavonoids such as orientin, quercetin, quercitrin, isoquercetin, vitexin, rutin, hyperoside, with others, including luteolin and pro-anthocyanidins to which the main pharmacological activities of the plant [31] Also, [32] reported that A. vulgaris contain flavonoids which important for the treatment of inflammation and wound healing. Our results are agree with [33] which reported that medicinal plant A. vulgaris serve as a vital source of potentially useful new compounds for the development of effective therapy to combat liver problems.…”
Section: Data Insupporting
confidence: 93%
“…polyphenols, tannins composed of some gallic and mostly ellagic acid, flavonoids such as orientin, quercetin, quercitrin, isoquercetin, vitexin, rutin, hyperoside, with others, including luteolin and pro-anthocyanidins to which the main pharmacological activities of the plant [31] Also, [32] reported that A. vulgaris contain flavonoids which important for the treatment of inflammation and wound healing. Our results are agree with [33] which reported that medicinal plant A. vulgaris serve as a vital source of potentially useful new compounds for the development of effective therapy to combat liver problems.…”
Section: Data Insupporting
confidence: 93%
“…The mechanism of hepatic injury invariably involves peroxidation of hepatocyte membrane fatty acids causing destruction of the cells and their intracellular organelles. Oxidative stress plays a pivotal role in the initiation and progression of hepatic damage following insult to a variety of hepatotoxins [60]. These toxicants damage the hepatocyte primarily by producing reactive oxygen species which form covalent bond with the lipid moiety of the hepatic cell membranes.…”
Section: Hepatoprotective Activities Of Extracts Of Plants From Africamentioning
confidence: 99%
“…Medicinal herbs have been used in folk medicine for a long time and they have played a promising role in the treatment and prevention of various human diseases (AL-ASMARI et al, 2014). Despite the therapeutic advantages of medicinal plants, their potential toxicity is not recognized by the general public or by many professional groups of traditional medicine (SOETAN; AIYELAAGBE, 2009).…”
Section: Introductionmentioning
confidence: 99%